ANALISIS CAPITAL ADEQUANCY RATIO (CAR), LOAN TO DEPOSIT RATIO (LDR), DAN RETURN ON ASSETS (ROA) TERHADAP TINGKAT SUKU BUNGA DEPOSITO BERJANGKA PADA BANK BUMN PERIODE 2009-2014 - Suratama, Isna Nurcahyani; Fitriani, Dyah (Jurnal Fokus Manajemen Bisnis, 2015)
This study aims to determine the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) and Return on Assets (ROA) on the interest rate for time deposits at state-owned banks in Indonesia in the 2009-2014 period. The sample used in this study is state-owned banks in Indonesia, as many as 4 banks. The sampling technique used was purposive sampling technique. The method used in this study is quantitative research and the data obtained are secondary data where the data is already available in report form. The analysis technique used is multiple linear regression, hypothesis testing (t test and F test) and the coefficient of determination test. The results of the analysis showed that partially the Capital Adequacy Ratio (CAR) showed a regression coefficient of -0.674775 with a prob value of 0.5915, which meant that the CAR had a negative and not significant effect on deposit rates, while the Loan to Deposit Ratio (LDR) showed a value of regression coefficient of 0.109967 with a value of prob. 0.6871 which means that the LDR has a positive and not significant effect on the interest rate on time deposits and Return on Assets (ROA) shows a value of -10,63718 with a prob. 0.4255 which means ROA has a negative and not significant effect on the interest rate on time deposits. Based on the F test shows a prob value of 0.300476 so that simultaneously, CAR, LDR and ROA have no significant effect on the interest rate on time deposits.